Potential of Endophytic Fusarium sp. Against Bacterial Wilt Disease in Tomato Plants - Nur Aini Mahfud; Ahmad Adibul Akrom; Arika Purnawati (Nusantara Science and Technology Proceedings, 2023)
Ralstonia solanacearum is a pathogen that causes bacterial wilt in tomato plants (Lycopersicum esculentum), can decrease production until 90%. The controls generally use chemical pesticides which are harmful to the environment and humans, so it is necessary alternative controls using endophytic Fusarium sp. The aim of the research was to determine the effect of endophytic Fusarium sp. to bacterial wilt. Endophytic Fusarium sp. was explored on tomato plant in Tlekung, Junrejo-Batu and taken systematically randomly then brought to the laboratory. Isolation of endophytic fungi was done by washing the plants with running water, cutting 1cm then was sterilized. The sample was planted on Potato Dextrose Agar (PDA) and incubated at 37°C for 48 hours, if its growth was purified on new media. Isolation of R. solanacearum was done by washing the stems, cutting 0.5 cm then sterilizing. The piece is put into a test tube, added 10 ml of sterile water until the bacterial mass comes out and dissolves in sterile water. The mass of bacteria in sterile water is shaken using vortex until suspension forms. The suspension was grown on TZC agar and incubated at 280C for 24 hours, if it grow was purified on new media. Application of endophytic Fusarium sp. carried out using immersing technique of the roots of tomato plant. Inoculation of R. solanacearum was done into sterile soil before the plant were planted. The study used completely randomized design (CRD) with control and isolate of endophytic Fusarium sp. as treatments with 3 repeat and conducted in the greenhouse of the Faculty of Agriculture UPN "Veteran" East Java. Observations are incubation period and disease intensity, data were analyzed using BNT 5%. The results show that endophytic Fusarium sp. delayed the period incubation and suppressed the intensity of bacterial wilt disease in tomato plants.